Creation of Demonstration Experimental Devices, Methods and Principles of Their Use in the Lecture Process (Eurasian Scientific Herald, 2022)
The creation of demonstration experimental devices when teaching physics in secondary schools, their use in lectures develops the ability to create innovative technologies (startup project) by increasing the intellectual potential of students, teaching students logical thinking. The main objective of ergonomic research is to increase the efficiency of mental and physical activity of the teacher and student. In the study of physics, physical experiments are of great importance, revealing to students the rich content of science